The Estimation of the Willingness to Pay for Air-Quality Improvement in Thailand - Waranan Tantiwat (MDPI AG, 2021)
Thailand has experienced severe air-quality problems for the past 10 years. Complicating this situation, the Thai government allocates an insufficient budget for the management of air pollution. Using the contingent valuation method, this paper estimates the willingness to pay for air-quality improvement in Thailand to reveal the benefits that people will gain if air-quality improves. The results show that the total benefits from air-quality improvement would be 18.8 billion baht in 2020. The Thai government can use these findings as a guideline to redistribute its budget to address air pollution more effectively.